Tanzania Seed Sector Development Strategy: inception report - Minde, I. J.; Silim, S. N.; Nyange, D. A.; Ijumba, C. K.; Kadigi, I.; Ires, Idil (International Water Management Institute (IWMI), 2024)
This report presents an official starting point to the co-creation of the Tanzania Seed Sector Development Strategy (TSSDS), a collaborative effort between the Ministry of Agriculture, ASPIRES Tanzania, USAID, and the International Water Management Institute (IWMI). Despite having a strong legislative background, Tanzania currently lacks an overarching seed strategy toward improving the seed industry and strengthening its position in the East and Southern Africa region. The sector encounters diverse challenges, such as poor coordination in the public sector and a disincentivized private sector leading to low availability, utilization, and distribution of improved seed varieties and a weak formal seed system. Addressing these and further challenges can foster food production and security and improve livelihoods in the country and the region. In this report, preliminary findings from the literature review, engagement with seed sector stakeholders, and the TSSDS inception meeting are summarized. The inception meeting under patronage of the Ministry of Agriculture took place in November 2023 in Arusha, Tanzania. Based on these findings, the report offers the theory of change, the logical framework, and the methodology, which will drive the joint formulation of the TSSDS, ultimately seeking to transform the enabling environment for a more productive industry.